2017
DOI: 10.1080/10888705.2017.1303381
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Relating to Companion Rabbits Relinquished to Two United Kingdom Rehoming Centers

Abstract: Rabbits are a common companion animal in the United Kingdom, and some reports have suggested that large numbers are relinquished to rehoming centers each year. This study aimed to investigate the characteristics of rabbits relinquished to 2 UK rehoming centers and explore reasons given for relinquishment. The centers contributed data for all rabbits who entered their center during 2013 (n = 205). Most rabbits (59.5%) were relinquished by a guardian. Similar numbers of males and females were relinquished, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 27 publications
9
25
1
Order By: Relevance
“…Of the 898 advertisements posted for rabbits aged over 16 weeks for which neuter status was given (mean age of 14 months), just 83 were neutered (9.2%) and 59 (6.6%) were micro chipped. The adverts for adult rabbits identified here could be considered to represent a relinquished population, which could explain the low levels of neutering, as has been shown elsewhere [ 22 ].…”
Section: Resultsmentioning
confidence: 61%
“…Of the 898 advertisements posted for rabbits aged over 16 weeks for which neuter status was given (mean age of 14 months), just 83 were neutered (9.2%) and 59 (6.6%) were micro chipped. The adverts for adult rabbits identified here could be considered to represent a relinquished population, which could explain the low levels of neutering, as has been shown elsewhere [ 22 ].…”
Section: Resultsmentioning
confidence: 61%
“…The Residential Instability dimension encompasses neighborhood fluctuations in terms of both housing and familial factors. Residential Instability predicted increased risk of surrender due to housing issues, which has been cited as a common issue motivating animal relinquishment (11), including with animals other than dogs and cats [e.g., rabbits; (48)]. Factors of Residential Instability have previously been identified as issues in pet ownership [such as being a renter; (49)].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of such characteristics can be identified by reasons why people relinquish their animals and factors that make an adoption successful. In a survey of shelter workers, Ellis et al (2017) found that people relinquish their animals due to changes in lifestyle (new house, new partner), lack of planning for animal’s basic needs and aggression towards people in dogs, often due to poor training and socialization [ 53 ]. Using vignettes Hill and Murphy found that the two characteristics most likely to impact dog adoption success were behavior and size [ 54 ].…”
Section: Discussionmentioning
confidence: 99%